(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The very specific „morphosyntax“ of the rainbow as a phenomenon has been an incentive for the development of its rich symbolism among many peoples, which, in turn, left traces in language and culture. Well-developed symbolism can be traced among nearly all Slavic peoples as well. However, with regard to the words that covered the meaning of the rainbow, the Macedonian language is presenting an interesting and peculiar feature. Namely, the predominating words have a completely different semantic and etymological provenance determined by an enforced impact from the Old Testament and (to a lesser degree) the New Testament tradition.